Isotopic signatures (δ 13C and δ15N) of muscle, carapace and claw in Phrynops geoffroanus (Testudines: Chelidae) - Thiago S. Marques (Zoologia (Curitiba), 2011)
The isotopic composition ( δ13C and δ 15N) of muscle, carapace and claw was determined from six wild individuals of Phrynops geoffroanus (Schweigger, 1812) in order to verify the variation between those tissues. The mean values of δ13C e δ 15N were, respectively, -19.48 ± 0.81‰ (-20.8 - -18.64‰) and 7.23 ± 0.67‰ (6.49 - 8.3‰) for muscle, -16.52 ± 0.98‰ (-17.88 - -15.43‰) and 7.29 ± 0.54‰ (6.74 - 7.97‰) for carapace and -18.57 ± 0.97‰ (-19.97 - -17.26‰) and 4.36 ± 0.33‰ (3.93 - 4.79‰) for claw. We found a significant difference for the tissues evaluated for both δ13C and δ15N. Muscle and claw were statistically similar and more depleted in 13C than the carapace. Nonetheless, claw was more depleted in 15N than muscle and carapace tissues. These results are likely related to differences in metabolic processes involved on each tissue formation. The description of the isotopic signatures variation in P. geoffroanus tissues provides a baseline for future investigations on the diet reconstruction of this species when more than one tissue is involved.